Three-Component Copper-Phosphonate-Auxiliary Ligand Systems: Proton Conductors and Efficient Catalysts in Mild Oxidative Functionalization of Cycloalkanes - Armakola, Eirini; Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Salcedo, Inés R.; Choquesillo-Lazarte, Duane; Cabeza-Díaz, Aurelio; Kirillova, Marina V.; Kirillov, Alexander M.; Demadis, Konstantinos D. (ACS publications, 2018)
The synthesis, structural characterization, topological analysis, proton conductivity, and catalytic properties are reported of two Cu(II)-based compounds, namely a dinuclear Cu(II) complex [Cu2(μ-VPA)2(phen)2(H2O)2]· 8H2O (1) (H2VPA = vinylphosphonic acid, phen = 1,10- phenanthroline) and a 1D coordination polymer [Cu(μ- SO4)(phen)(H2O)2]∞ (2). Their structural features and Hbonding interactions were investigated in detail, showing that the metal−organic structures of 1 and 2 are extended by multiple hydrogen bonds to more complex 2D or 1D Hbonded architectures with the kgd [Shubnikov plane net (3.6.3.6)/dual] and SP 1-periodic net (4,4)(0,2) topology, respectively. These nets are primarily driven by the H-bonding interactions involving water ligands and H2O molecules of crystallization; besides, the (H2O)4/(H2O)5 clusters were identified in 1. Both 1 and 2 are moderate proton conductors, with proton conductivity values, σ = 3.65 × 10−6 and 3.94 × 10−6 S·cm−1, respectively (measured at 80 °C and 95% relative humidity). Compounds 1 and 2 are also efficient homogeneous catalysts for the mild oxidative functionalization of C5−C8 cycloalkanes (cyclopentane, cyclohexane, cycloheptane, and cyclooctane), namely for the oxidation by H2O2 to give cyclic alcohols and ketones and the hydrocarboxylation by CO/H2O and S2O82− to the corresponding cycloalkanecarboxylic acids as major products. The catalytic reactions proceed under mild conditions (50−60 °C) in aqueous acetonitrile medium, resulting in up to 34% product yields based on cycloalkane substrate.
Keywords: Conductividad eléctrica; Hidrocarburos; Copper-Phosphonate; Proton-conductivity